Tuan Guru's communication strategy in resolving religious ideological conflict in Lombok, Indonesia - Pardi, Muh. Habib Husnial (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose – This article attempts to explain Tuan Guru's communication strategy in conflict resolution between Islamic groups in Lombok, namely between communities affiliated with the Nahdlatul Wathan organization versus the Sunnah (Wahhabi) group.Method – This article uses a qualitative method-case study. Data were collected through observation, documentation, and interviews and then analyzed through the stages of condensation, display, interpretation, and conclusion.Result – The results of this study show that the source of conflict that occurs in the community is the difference in religious ideology between Aswaja Islam and Wahhabi Islam. Second, the master teacher was able to mediate the conflict by using religious and cultural communication strategies. He campaigned for peace values derived from Islamic teachings and strengthened socio-cultural capital as a tool for harmony, such as silaturrahim in the tradition of begawe (feast) of marriage, birth, and death.Implication – This article contributes to the study of Tuan Guru employs a communication strategy that emphasizes dialogue and mutual understanding, facilitating open discussions to bridge gaps between differing religious ideologies. By fostering a respectful exchange of perspectives, he creates a platform for resolving conflicts and promoting religious harmony.Originality/Value – This research exploration of tuan guru not only as a leader of the pesantren but also as a